Overview of COMFA+FISH instant porridge macronutrients - Tolar-Peterson, Terezie; Ragsdale, Kathleen; Mudege, Netsayi; Banda, Sylvia; Muzungaire, Lizzy; Burdine, Madeline; Roman, Katie; Bowen, Jadyn (Mississippi State University, Feed the Future Innovation Lab for Fish, 2024)
These results included a nutrient analysis of locally sourced Kapenta DFP, two sensory panels of dishes fortified with a DFP-based protein/micronutrient blend we call Complementary Food for Africa+Dried Fish Powder (ComFA+Fish), collaboration with our private sector partner in Zambia, Sylva Food Solutions, to produce ComFA+Fish Plain and Vanilla Instant Porridges, and a third sensory panel to test the acceptability of the porridges among adults prior to testing their acceptability among IYC in 2024.